Development of Student Worksheets Based on Science Process Skills on Excretory System Concepts - Muhammad Fadhlan Mumtaza; Zulfiani Zulfiani (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to produce a student worksheet based on Science Process Skills (SPS) on the concept of the excretory system and to see the responses of teachers and students to the worksheet. The method used is Research and Development (R&D) with a 4D development model (Define, Design, Develop, Disseminate), which is modified into 3D (without Disseminate). The instruments used in this study included a checklist of student worksheets, interview sheets, content validity and readability test instruments for student worksheets, and teacher and student response questionnaires. The development process was through a validity test by three experts, a readability test by 12 students, and a field trial by one biology teacher and 90 students. The results showed that the developed worksheet had an average validity percentage of 85.40% with excellent criteria. In the readability test, the average percentage of the worksheet reached 92.01%, with excellent criteria as well. While in the field trial, the responses of teachers and students showed excellent criteria with percentages of 87.42% and 86.65%. Based on the results, it can be concluded that the Student Worksheet is very suitable to be used in learning activities